Implementing Health Impact Assessment at National Level: An Experience in Iran - Behzad DAMARI; Abbas VOSOOGH-MOGHADDAM; Sahand RIAZI-ISFAHANI (Tehran University of Medical Sciences, 2018)
Background: According to the general health policies issued in 2014, Health Impact Assessment (HIA) or Health Annex should be implemented in Iran. The present study provided a model for executing HIA in the Iranian context as a developing country. Methods: This is a system design study with the qualitative approach. The data on the system components were gathered via reviews of the literature, in-depth interviews and focused group discussions (FGDs) with experts. The information were contently analyzed in order to draft the model and a consensus was reached on by the steering committee.  Results: Fifteen in-depth interviews and six FGD meeting were conducted. The equity-based approach in assessing the health impacts of policies, programs and projects were chosen as the most practical tool. Experts believe that for the next five years, HIA should be used just for the "national projects" so that the ministries and national agencies could be empowered. Components of the model including structure, procedures, and standards, management style, mission and resources were prepared. The national regulations and protocols were sent to the SCHFS Secretariat for final revision and the council approval. Conclusion: The hasty implementation of HIA will face serious resistances as the health-oriented attitude and behavior in both government and non-governmental sectors will gradually form. Also, the overlapping of the contents of HIA with other tools such as Environmental, Cultural and Social Impact Assessments, currently used by other sectors, causes difficulties in implementing the HIA by the Ministry of Health and Medical Education.